2018
DOI: 10.19080/gjidd.2018.04.555648
|View full text |Cite
|
Sign up to set email alerts
|

Not All Those Who Wander are Lost: Examining the Character Strengths of Dyslexia

Abstract: The number of students and people with dyslexia and other learning differences has been steadily increasing in recent years. This has led to an accompanying need for additional support for people with dyslexia. Whilst acknowledging that support is vital for people with dyslexia, it is also important to identify the strengths that people with dyslexia have that help individuals flourish. For many years, dyslexia research has been more pre-occupied in exploring the problems faced by people with dyslexia. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…A previous study (27) found the top five strengths were honesty, kindness, fairness, humor, and gratitude, and the bottom five strengths were forgiveness, humility, spirituality, zest, and self-regulation in people with multiple sclerosis. In another study, authors found that the most common character strengths were curiosity, fairness, kindness, judgment, honesty, and leadership, while the least common character strengths were zest, prudence, perseverance, humility, hope, self-regulation, and spirituality in people with dysclexia (37). These results are partially consistent with our findings; however, it is also important to highlight that the most and least common character strengths may change based on disability groups.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study (27) found the top five strengths were honesty, kindness, fairness, humor, and gratitude, and the bottom five strengths were forgiveness, humility, spirituality, zest, and self-regulation in people with multiple sclerosis. In another study, authors found that the most common character strengths were curiosity, fairness, kindness, judgment, honesty, and leadership, while the least common character strengths were zest, prudence, perseverance, humility, hope, self-regulation, and spirituality in people with dysclexia (37). These results are partially consistent with our findings; however, it is also important to highlight that the most and least common character strengths may change based on disability groups.…”
Section: Discussionsupporting
confidence: 90%
“…Dessa forma, compreendemos que a ciência psicológica é capaz de trazer possibilidade de mudanças de comportamentos humanos e dos processos mentais, ao prever e controlar variáveis associadas ao comportamento e as emoções. Focaremos, neste estudo, no campo da Neuropsicologia e Psicologia Positiva que vem se destacar por suas relevantes contribuições para o campo da dislexia (SILVA, 2018;KANNANGARA et al, 2018; GOSSE; DRICOT; VAN REYBROECK, 2022).…”
Section: Contribuições Da Neuropsicologia E Da Psicologia Positiva Pa...unclassified
“…Além disso, segundo Magyar-Moe, Owens e Conoley, (2015), a Psicologia Positiva ancora-se à luz da teoria das virtudes e forças do caráter (o desenvolvimento das forças pode colaborar com uma experiência mais frequente de estados emocionais positivos, estabelecimento de relacionamentos interpessoais mais saudáveis e engajamento maior em atividades acadêmicas), dedicando-se na construção dos pontos fortes enquanto gerencia e busca minimizar os fracos. Nessa direção, Kannangara et al (2018) expressam que o foco principal do aporte teórico da PP tem sido acerca de como a dislexia é vista, não como uma deficiência que reside dentro de um indivíduo, mas sim como uma interação entre as habilidades da pessoa e as demandas do ambiente.…”
Section: Humanas E Sociaisunclassified
“…Their visual thinking interferes with the spoken language and may lead to dyslexia or autism. In both these conditions, visual thinking is known to be strongly present [58][59][60][61][62][63][64][65][66][67]. In the case of dyslexia, the child has problems with utilizing spoken language; in autism spoken language is partially or sometimes completely rejected.…”
Section: Visual Language In Childrenmentioning
confidence: 99%